Marangoni convection in a horizontal liquid layer with insoluble surfactant / Ainon Syazana Ab Hamid - Ab Hamid, Ainon Syazana (2013)
Thermocapillary (Marangoni) convection either steady or oscillatory is known to cause imperfection in the quality of products. The dynamics of the convective motion in a thin fluid layer and the gradients of the surface tension can be significantly altered by the presence of insoluble surfactant, internal heat generation and the application of a feedback thermal controller. In this study, linearly dependent surface tension gradient on temperature and surfactant concentration with the effects of thermal feedback control and internal heat generation are considered to examine the instability of the steady Marangoni convection. The objectives of this study are to analyze theoretically the effect of heat generation and feedback control on Marangoni convection in a horizontal liquid layer with insoluble surfactant. The layer is bounded from below by a rigid heat-conducting plate and above by a free surface. The linear stability theory of the system is performed to undertake a detail investigation. The critical Marangoni numbers for condition of uniform heat flux revealed lower values' in contrast to uniform temperature condition. The system with uniform temperature condition is more stable than the condition of uniform heat flux. Small controller gains are able to stabilize the system but large controller gain becomes a destabilizing factor. Internal heat source destabilizes the system and insoluble surfactant of low concentration has a stabilizing effect. The ability to control by either delaying or advancing the onset of instability can lead to better material processes and achieve optimum outcomes.